Road transport infrastructure of republic of Karelia automobile roads: assessment of the state and development trends - Fedorova Anastasia; Kuzmenkov Aleksandr; Emelianova Elena (E3S Web of Conferences, 2023)
This study was conducted as part of the possibility consideration of forming a production and construction cluster in the Republic of Karelia. The paper presents the analysis results of the Republic of Karelia transport infrastructure state. Special attention is paid to the road transport infrastructure state and the territory provision with automobile roads and traffic flows maintenance services analysis. The article presents graphic materials, compiled by the authors characterizing the road surface type of public roads and transport provision level in the context of the region municipalities. Methods of economic and mathematical modeling, retrospective and statistical analysis are used in the study. Data from the Federal and Territorial State Statistics Service, the Federal Road Agency (Rosavtodor), as well as data from reports of local self-government bodies of the districts of the Republic of Karelia was used as information base of the study. The study provides statistical data overview for the period from 1998 to 2021. The data for the period from 2017 to 2021 and the indicators of 2021 are analyzed in more detail. The assessment of the region's road transport infrastructure state in the context of its use for the formation of a production and construction cluster was carried out.